2015
DOI: 10.1111/jgs.13376
|View full text |Cite
|
Sign up to set email alerts
|

Diet Soda Intake Is Associated with Long‐Term Increases in Waist Circumference in a Biethnic Cohort of Older Adults: The San Antonio Longitudinal Study of Aging

Abstract: BACKGROUND/OBJECTIVES Diet soda (DS) intake (DSI) has been associated with increased cardiometabolic risk, but its specific impact in older adults has not been addressed. Because central obesity increases cardiovascular risk, we examined the relationship between DSI and long-term waist circumference (WC) change (ΔWC) in the bi-ethnic San Antonio Longitudinal Study of Aging (SALSA). DESIGN Prospective cohort study. SETTING San Antonio, Texas, neighborhoods PARTICIPANTS SALSA examined 749 Mexican-American … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
71
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(80 citation statements)
references
References 50 publications
7
71
0
2
Order By: Relevance
“…From 11 774 citations, we assessed 938 full-text articles for eli gibility, and 37 studies involving a total of 406 910 individuals met our inclusion criteria: 7 RCTs 19,20,34-38 and 30 cohort studies [14][15][16][17][18][21][22][23][24] ( Figure 1). 36,37 or consumption of aspartame at the discretion of the participant.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…From 11 774 citations, we assessed 938 full-text articles for eli gibility, and 37 studies involving a total of 406 910 individuals met our inclusion criteria: 7 RCTs 19,20,34-38 and 30 cohort studies [14][15][16][17][18][21][22][23][24] ( Figure 1). 36,37 or consumption of aspartame at the discretion of the participant.…”
Section: Resultsmentioning
confidence: 99%
“…13 Several studies involving more than 100 000 new participants and representing several new geographic settings have since been published. [14][15][16][17][18][19][20][21][22][23][24] Our objective was to synthesize evidence addressing this question: Is routine consumption of nonnutritive sweeteners by adults and adolescents associated with adverse long-term cardiometabolic effects in RCTs and prospective cohort studies?…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, several studies including a recent systematic review and meta-analysis, 10 have linked diet soft drinks with poor cardiovascular outcomes. 3,[11][12][13][14][15][16] The population-based Multi-Ethnic Study of Atherosclerosis (MESA), for example, found that a daily consumption of diet soda was associated with 36% and 67% greater relative risks of incident metabolic syndrome and type 2 diabetes mellitus, respectively, compared with non-consumption. 12 Although plausible biological mechanisms explaining these associations are limited, it is possible that artificial sweeteners in diet soft drink increase the need for sweet, energy-dense foods or beverages 17 and disrupt an individual's ability to accurately estimate energy intake and energy needs, 18 both of which may lead to increased consumption of calories.…”
Section: Introductionmentioning
confidence: 99%